"Do You Want to Negotiate with Me?"- Avoiding and Dealing with Conflicts Arising in Conversations with the Young Unemployed - Daniela Boehringer; Ute Karl (Social Work and Society, 2015)
This paper addresses conflict talk in social services. We focus on naturally occurring face-to-face conversations between claimants and personal contact persons in German job centres for young people under the age of 25. Using conversation analysis we identify conflict episodes arising in these conversations. We show how the participants display disagreement/agreement and how they escalate or terminate conflict episodes. We show that participants tend to avoid full confrontation in co-present interaction (both the 'customer' and the 'personal contact person'). They tend to maintain social continuity. On the other hand, many 'customers' file a complaint against the decisions of job centres concerning their unemployment benefits. There seems to be a lack of conflict solution potential in this social service organisation. There are not enough intermediate ways to deal with conflicts, which interactants tend to avoid but which are of course still there.